Analysis of Association Between the Insertion Location of Iris Root and Narrow Angle. Issue 6 (August 2015) - Wang, Bingsong; Nongpiur, Monisha E.; Liu, Jing; Dong, Ning; Aung, Tin
Abstract : Aim: To study the association between the insertion location of iris root and narrow angle. Methods: This was a prospective observational study. A total of 142 eyes of 142 subjects were recruited, including 78 with narrow angles and 64 normals. All participants underwent ultrasound biomicroscopy and customized software was used to quantitatively analyze the images. An eye was considered to have narrow angle if there was iridotrabecular contact for at least 180 degrees on nonindentation gonioscopy in the primary position. The difference in various parameters between subjects with narrow angle and normal controls were analyzed. The association between the distance from the iris root to scleral spur (IrisD) and angle open distance was also analyzed. Results: Significant differences between narrow angle and normal eyes were found for anterior chamber depth (ACD, 2.01±0.26 vs. 2.66±0.34 mm, P ⩽0.001), anterior chamber width (ACW, 10.96±0.45 vs. 11.19±0.39 mm, P =0.003), IrisD (0.083±0.091 vs. 0.174±0.094 mm, P <0.001), and iris thickness at 1500 µm from the scleral spur (IT1500, 0.533±0.087 vs. 0.503±0.081 mm, P =0.007). After adjusting for age, sex, ACD, ACW, and IT1500, a smaller IrisD was associated significantly with narrow angle (odds ratio, 104.3; 95% confidence interval, 5.9-1852, comparing highest with lowest quartile). In terms of distinguishing narrow angle subjects from open angle subjects, IrisD [area under the receiver operator characteristic curve (AUC) 0.76] performed relatively poorer compared with ACD (AUC 0.95). Conclusions: A smaller distance from iris root to scleral spur was associated with the presence of narrow angle.